Extensively and multidrug-resistant bacterial strains: case studies of antibiotics resistance - Almutairy, Bandar (Frontiers in Microbiology, 2024)
The development of antibiotic resistance compromises the effectiveness of our most effective defenses against bacterial infections, presenting a threat to global health. To date, a large number of research articles exist in the literature describing the case reports associated with extensively drug resistance (XDR) and multidrug resistance (MDR) bacterial strains. However, these findings are scattered, making it time-consuming for researchers to locate promising results and there remains a need for a comparative study to compile these case reports from various geographical regions including the Kingdom of Saudi Arabia. Additionally, no study has yet been published that compares the genetic variations and case reports of MDR and XDR strains identified from Saudi Arabia, the Middle East, Central Europe, and Asian countries. This study attempts to provide a comparative analysis of several MDR and XDR case reports from Saudi Arabia alongside other countries. Furthermore, the purpose of this work is to demonstrate the genetic variations in the genes underlying the resistance mechanisms seen in MDR and XDR bacterial strains that have been reported in Saudi Arabia and other countries.To cover the gap, this comprehensive review explores the complex trends in antibiotic resistance and the growing risk posed by superbugs. We provide context on the concerning spread of drug-resistant bacteria by analyzing the fundamental mechanisms of antibiotic resistance and looking into individual case reports. In this article, we compiled various cases and stories associated with XDR and MDR strains from Saudi Arabia and various other countries including China, Egypt, India, Poland, Pakistan, and Taiwan. This review will serve as basis for highlighting the growing threat of MDR, XDR bacterial strains in Saudi Arabia, and poses the urgent need for national action plans, stewardship programs, preventive measures, and novel antibiotics research in the Kingdom.